Development of monospecific polyclonal antibodies against hypervirulent Klebsiella pneumoniae : - darniati darniati; Surachmi Setiyaningsih; Dewi Ratih Agungpriyono; Ekowati Handharyani (Society for Indonesian Biodiversity, 2021)
Abstract. Darniati, Setiyaningsih S, Agungpriyono DR, Handharyani E. 2021. Development of monospecific polyclonal antibodies against hypervirulent Klebsiella pneumoniae. Biodiversitas 22: 99-105. The aim of the research was to produce monospecific antibodies against Klebsiella pneumoniae serotype K1 and K2. Klebsiella pneumonia isolates were recovered from pneumonic lungs of Aceh cattle. The bacteria were identified by rpoB (RNA polymerase ? subunit) PCR amplification specific for K. pneumoniae. The presence of  capsule cluster gene magA  and k2A  was used to characterize capsular serotype K1 and K2, respectively. Antisera were produced using serial immunization of New Zealand White rabbits with K. pneumoniae serotypes K1 and K2. The presence of antibodies was determined by using immunodiffusion test and purification was performed by immunoaffinity purification method. K. pneumoniae antibodies began to appear on the 14th day after the first injection and progressively intensified after the 1st and 2nd booster. The cross-reactivity between the antigen was eliminated by absorbing the antisera with the opposite antigen and several serotypes of non-K1/K2. After purification, serum protein concentrations were substantially decreased from 58.48 µg/µL and 53.99 µg/µL to 2.38 µg / µL and 3.72 µg / µL for K1 and K2, respectively). The SDS-PAGE analysis showed two bands with molecular weight at 54 kDa and 25 kDa representing the heavy and light chains of immunoglobulin G, respectively. Purified polyclonal antiseras against K. pneumoniae serotypes K1 and K2 showed high affinity and specificity for homologous antigens in immunodiffusion and direct agglutination tests, and immunohistochemical staining.